Estimating the economic impacts of rural tourism in Semporna, Sabah, Malaysia - Chia, Kei Wei; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
This study describes the methodology used to achieve the research objective through collecting primary and secondary data in Semporna, Sabah, Malaysia. This study will employ on-site survey and primary data on tourists. Business expenditure will also be collected to estimate the total economic impacts of rural tourism in Semporna. By using the input-output (I-O) model, the results obtained from tourists and business operators can be used to estimate the total economic impacts. The tourist questionnaire will be divided into four sections based on 26 descriptive questions, in both open-ended and closed-ended forms; a) expenditure by categories; b) package tour; c) non-package tour; and d) demographic, socio-economic, and psychological characteristics of respondents. On top of that, business operators are asked to indicate the type of business, ownership, the initial capital used to start their business, the average revenue and spending of their business, number of employees and their positions, as well as the average wage or salary. The secondary data will also be obtained from various government agencies to fulfil the data requirement of the analysis of the input-output model. The economic impacts of tourism will be calculated using the I-O model, with the use of the IMPLAN software. The I-O multipliers will, in turn, be derived from the latest 2005 Malaysia I-O tables. Finally, the issues of reliability and validity of measurement scales will be addressed.